2018
DOI: 10.3390/sports6020035
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between Elite Wrestlers’ Leg Strength and Balance Performance, and Injury History

Abstract: The purpose of this study is to examine the correlation between leg power and balance performance in elite wrestlers and injury history. In the research group, there are 18 elite freestyle male wrestlers at the ages of 24.27 ± 3.18 years, with a height of 171.86 ± 5.44 cm and a body weight of 79.27 ± 11.16 kg. Information on the injury history of the athletes’ upper legs for the past year was collected via interviews with the club’s physiotherapist. Laboratory tests to measure performance assessed height, body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In addition, the statistical difference between H/Q ratios (p<0.05) shows that taekwondo athletes have lower H/Q strength ratios. In previous isokinetic studies, it was determined that the knee isokinetic strength of taekwondo (Choi et al, 2021;El-Ashker et al, 2022;Hammami et al, 2013;Harbili et al, 2022;Kang et al, 2021) and wrestling (Çimen Polat et al, 2018;Drid et al, 2009;Hoseini et al, 2022;Kraemer et al, 2001;Tatlici, 2021;Tatlici et al, 2021) athletes supported our research results. This result may be due to the fact that taekwondo explosively trains roundhouse and rotating kicks that require lower extremity FLX and EXT strength.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, the statistical difference between H/Q ratios (p<0.05) shows that taekwondo athletes have lower H/Q strength ratios. In previous isokinetic studies, it was determined that the knee isokinetic strength of taekwondo (Choi et al, 2021;El-Ashker et al, 2022;Hammami et al, 2013;Harbili et al, 2022;Kang et al, 2021) and wrestling (Çimen Polat et al, 2018;Drid et al, 2009;Hoseini et al, 2022;Kraemer et al, 2001;Tatlici, 2021;Tatlici et al, 2021) athletes supported our research results. This result may be due to the fact that taekwondo explosively trains roundhouse and rotating kicks that require lower extremity FLX and EXT strength.…”
Section: Discussionsupporting
confidence: 84%
“…Uğur et al [ 16 ] declared that as the strength of leg muscle increases, the injury risk decreases, it has also been reported that the proportion between hamstring and quadriceps muscles in freestyle wrestlers’ upper leg strength values is not ideal. Addressing that injury risk increases with loss of strength [ 17 ]. Studies have shown that eccentric quadriceps strength and low eccentric flexor/extensor ratio are related to an increase in anterior cruciate ligament injury risk, and emphecized that H/Q values should be determined to prevent injuries, and also for rehabilitation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%